Uneingeschränkte Solidarität: Das neue strategische Konzept der NATO und die Außen- und Sicherheitspolitik der Bundesrepublik Deutschland - Strutynski, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
This article focuses on the analysis of the new strategic concept of NATO (Lisbon 2010) and its effect on German foreign and security policy. During the Cold War, the (old) Federal Republic of Germany had done well to recognize its limited sovereignty while at the same time expanding its economic and political influence in NATO and the EC/EU. This approach has not fundamentally changed with the unification of Germany in 1990. Since then Germany has been developing its imperial ambitions cautiously, embedded in the aggressive NATO military pact and the militarization of the EU. The credo of the new Germany is the enforcement of both;, German economic and geo-strategic interests as a nation cannot be achieved alone, but only within the range of existing alliances.